Low-density high-shrinkage film as well as preparation method and application thereof
By developing a low-density and high-shrinkage film composed of polypropylene homopolymer, cycloolefin copolymer, terpolymer polypropylene and silicone, the problem that bottle-type label materials cannot be separated from the PET bottle body during the recycling process in the prior art is solved, and efficient PET bottle sheet recycling and suitable label sleeve effects are achieved.
Patent Information
- Application Number
- CN202510184857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-08
AI Technical Summary
The existing bottle-type label shrinkage materials cannot be separated from the PET bottle during physical recycling, resulting in low recycling efficiency and high density of some materials, which has problems of environmental protection and application value.
A low-density high-shrinkage film is developed, which consists of a core layer structure composed of polypropylene homopolymer and cycloolefin copolymer and a surface layer structure composed of terpolymer polypropylene and silicone, with a density of <1.0 g/cm3 and a lateral shrinkage rate of ≥70%.
The separation of film and PET bottle body during physical recycling is achieved, ensuring high-quality recycling of PET bottle pieces, with good environmental protection significance and social value, and has high shrinkage and stiffness, which is suitable for bottle label sleeve applications.
Smart Images

Figure CN119773335A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a low-density high-shrinkage film and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, polyvinyl chloride (PVC), polyethylene terephthalate-1,4-cyclohexane dimethanol (PETG), and oriented polystyrene (OPS) shrink films are the main shrink materials in the field of bottle label shrink packaging. In terms of raw material manufacturing, the manufacturing of PVC raw materials is a high-energy consumption project, and it will produce international first-class carcinogens during heating or incineration; OPS shrink film raw materials have a narrow application field due to the harshness of ink systems and temperatures during application; PETG shrink film materials only contain three substances, C, H, and O, and are mainly derived from petroleum, and are currently the mainstream shrink film.
[0004] In the physical recycling system, bottle labels and bottles are recycled together and will go through the "crushing-cleaning" process. The main material of beverage bottles is polyetherimide (PET), with a density of 1.4g / cm 3 The density of PVC shrink labels is 1.38-1.40g / cm 3 The density of OPS shrink labels is 1.04-1.09g / cm 3 The density of PETG shrink labels is 1.28-1.32g / cm 3 , and the density of water in the cleaning process is 1.0g / cm 3 Therefore, these three mainstream shrink label materials will sink with the PET bottle itself during the "crushing-washing" of physical recycling and cannot be separated from the bottle.
[0005] Therefore, the technical personnel in this field urgently need to find a low-density high-shrink film that can be used as a beverage bottle label, which can ensure that the film has both the shrinkage characteristics of the current mainstream shrink film (transverse shrinkage ≥ 70%) and a density of <1.0 g / cm 3 The lower density makes it possible to separate the label containing ink from the clean PET bottle in the "crushing-washing" stage of physical recycling, which will have very important environmental significance and application value. Summary of the invention
[0006] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a low-density high-shrinkage film and its preparation method and application. The low-density high-shrinkage film provided by the present invention has a high shrinkage effect similar to that of petroleum-based PETG shrinkage film (lateral shrinkage ≥ 70%), which can achieve good results in the process of shrinking bottle labels. On the other hand, the film density is less than 1.0g / cm 3 , it is separated from the PET bottle in the "crushing-cleaning" stage of physical recycling, achieving high-quality PET bottle recycling, which has good environmental significance and social value.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] A first aspect of the present invention provides a low-density high-shrinkage film, comprising a core layer structure and a surface layer structure arranged on the surface of the core layer structure;
[0009] The raw materials of the core layer structure include polypropylene homopolymer and cycloolefin copolymer; the raw materials of the surface layer structure include terpolymer polypropylene and silicone;
[0010] The density of the low-density high-shrink film is less than 1.0 g / cm 3 , the transverse shrinkage rate in a 90℃ water bath for 10s is ≥70%.
[0011] It should be noted that the term transverse shrinkage refers to the shrinkage direction of the film being parallel to its width.
[0012] In some embodiments of the present invention, the thickness ratio of the upper surface structure, the core layer structure and the lower surface structure of the low-density high-shrink film is 5-10:80-90:5-10, preferably 10-20:60-80:10-20. In this thickness range, the obtained film can have a low density, a high shrinkage rate and high stiffness (bending modulus>3500MPa), and can ensure smooth sleeve labeling of the film in sleeve applications.
[0013] In some embodiments of the present invention, the thickness of the low-density high-shrink film is 50-100 μm. Within this range, the low-density high-shrink film can maintain a certain stiffness to avoid being too soft to be smoothly sleeved, thus affecting its use as a label.
[0014] In some embodiments of the present invention, the density of the low-density high-shrink film is 0.92-0.99 g / cm 3 The film has a lower density than water, which facilitates separation from the PET bottle in the downstream physical recycling field, ensuring the quality stability of the PET bottle flakes in the subsequent recycling process.
[0015] In some embodiments of the present invention, in the core layer structure, the mass ratio of polypropylene homopolymer to cycloolefin copolymer is 60-90:10-40. The addition of cycloolefin copolymer improves the hardness of high crystallinity polypropylene homopolymer, ensures that the obtained film has a certain stiffness, and avoids the phenomenon of label sticking when it is used as a label.
[0016] In some embodiments of the present invention, the polypropylene homopolymer has a crystallinity of 60-80%, a melt flow rate of 5-20 g / 10 min at 230° C. and 2.16 kg, an elastic modulus of 2000-3000 MPa, and a Vicat softening point of 130-170° C.
[0017] In some embodiments of the present invention, the cycloolefin copolymer has a melt flow rate of 5-20 g / 10 min at 230° C. and 2.16 kg, and a density of 0.92-0.99 g / cm 3 , the glass transition temperature is 110-150℃.
[0018] In some embodiments of the present invention, in the surface layer structure, the content of organic silicon is 0.1-0.5% of the total mass of the surface layer structure.
[0019] In some embodiments of the present invention, the particle size of the organosilicon is 0.5-1.0 μm.
[0020] In some embodiments of the present invention, the organic silicon includes one of vinyl silane, amino silane and methacryloxy silane.
[0021] In some embodiments of the present invention, the melt flow rate of the terpolymer polypropylene at 230°C and 2.16kg is 3-10g / 10min, and the melting point is 130-170°C. The terpolymer polypropylene is ethylene-propylene-1-butene terpolymer polypropylene, and the content of ethylene and butene-1 in the terpolymer polypropylene is 10-30wt%.
[0022] The second aspect of the present invention provides a method for preparing the above-mentioned low-density high-shrinkage film, comprising:
[0023] The organic silicon and the terpolymer polypropylene are melt blended and extruded and then pelletized to obtain the raw material of the surface structure;
[0024] The raw material of the core layer structure is obtained by mixing the polypropylene homopolymer and the cycloolefin copolymer according to a certain proportion;
[0025] The raw materials of the surface layer structure and the raw materials of the core layer structure are melted, cast, longitudinally stretched and transversely stretched to obtain a low-density high-shrinkage film.
[0026] In some embodiments of the present invention, the preparation method includes using a twin-screw extruder with a length-to-diameter ratio of 40-52:1, accurately feeding the ternary copolymer polypropylene from the twin screw from the feed port, and side-feeding the silicone in the melt plasticizing zone of the twin-screw extruder according to proportion. The extrusion temperature is 120-180°C, and the extruded mixed melt is pelletized and dried underwater to obtain the raw material of the surface structure.
[0027] In some embodiments of the present invention, the melting includes using a twin-screw extruder with a length-to-diameter ratio of 38-46:1 to melt and plasticize the raw materials of the surface layer structure and the raw materials of the core layer structure respectively, and the extrusion temperature is 130-200°C.
[0028] In some embodiments of the present invention, the casting includes the raw materials of the surface structure and the raw materials of the core structure. The melts are filtered and then flow out of the adapter and the die head. They are then cooled on a quench roller at 30-50°C under a wind knife with a wind pressure of 40-80kPa and a wind knife gap of 1-3mm to form a casting.
[0029] In some embodiments of the present invention, the longitudinal stretching comprises longitudinally stretching the cast sheet by 1.01-1.6 times after preheating, and the longitudinal stretching temperature is 60-100°C; preferably, the preheating is preheating the cast sheet by a roller at 60-120°C.
[0030] In some embodiments of the present invention, the transverse stretching includes preheating the longitudinally stretched film again and then stretching it transversely by 6.0-10.0 times, and the transverse stretching temperature is 80-120 degrees Celsius; preferably, the preheating temperature of the preheating again is 90-130°C.
[0031] In some embodiments of the present invention, after the transverse stretching is completed, a low-density high-shrinkage film is obtained by heat setting treatment and cooling treatment; wherein the temperature of the heat setting treatment is 80-100°C, and the temperature of the cooling treatment is 30-40°C.
[0032] The third aspect of the present invention provides a use of the above-mentioned low-density high-shrinkage film or the low-density high-shrinkage film prepared by the above-mentioned preparation method in bottle label materials.
[0033] In some embodiments of the present invention, the density of the bottle is greater than 1 g / cm 3 , further preferably, the bottle is made of polyethylene terephthalate.
[0034] A fourth aspect of the present invention provides a label, wherein the low-density high-shrink film or the low-density high-shrink film prepared by the above-mentioned preparation method is made into a sleeve and is sleeved around the outer periphery of the packaging object.
[0035] In some embodiments of the present invention, the packaging object is a bottle, preferably a beverage bottle, and the material of the beverage bottle is polyethylene terephthalate.
[0036] In some embodiments of the present invention, during the preparation of the sleeve, a solvent is used to self-bond the low-density high-shrinkage film together. Further preferably, the solvent is selected from at least one of tetrahydrofuran, chloroform and acetone.
[0037] The beneficial effects of the present invention are:
[0038] The present invention provides a low-density high-shrinkage film, which has a special three-layer structure, a transverse shrinkage rate of ≥70%, and an overall density of 0.92-0.99 g / cm 3 , which is conducive to separation from PET bottles in the downstream physical recycling field, and 1.28-1.32g / cm 3 Compared with high-density PETG shrink film, the density is greatly reduced, which saves the amount of petroleum-based polymer resin and ensures the quality stability of PET bottle flakes in the subsequent recycling process.
[0039] The surface structure of the low-density high-shrink film provided by the present invention adopts a mixed resin of terpolymer polypropylene containing ethylene and butene-1 and silicone, the resin has the printability of multi-color ink and has high adhesion under solvent, and can be conveniently made into a sleeve for sleeve labeling; the core layer structure adopts a mixed resin of high-crystallinity polypropylene homopolymer and cycloolefin copolymer, which ensures that the film has good stiffness (bending modulus>3500MPa) and shrinkage characteristics of more than 70% under high-multiple stretching. The film prepared by the present invention through specific olefin materials, structures and processes can ensure the smooth sleeve labeling and shrinkage effect of the film in sleeve applications, and the preparation method has universal applicability and is easy to mass-produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0041] Figure 1 This is the structure of the low-density high-shrinkage film prepared in an embodiment of the present invention.
[0042] Among them, 1-surface structure, 2-core structure. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0044] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0045] The sources of the raw materials used in the following examples are shown in Table 1.
[0046] Table 1 Raw material information table used in the examples
[0047]
[0048]
[0049] Embodiment 1: A method for preparing a low-density high-shrinkage film, comprising the following steps:
[0050] The terpolymer polypropylene and the organosilicon with a particle size of 0.5 μm are mixed in a mass ratio of 99.6:0.4 in a twin-screw extruder with an aspect ratio of 40:1 and an extrusion temperature of 120℃-180℃ (containing 6 heating zones, gradually heating from 120℃ to 180℃ according to "120℃-130℃-140℃-150℃-160℃-170℃-180℃"). Among them, the terpolymer polypropylene resin is accurately fed from the feed port by the twin screw, and the organosilicon is side-fed in the melt plasticization zone of the extruder. Finally, the mixed melt is pelletized and dried underwater to obtain the raw material of the surface structure of the terpolymer polypropylene resin and the organosilicon mixed (hereinafter referred to as A layer material).
[0051] The above-mentioned A layer material is added into a twin-screw extruder with a length-to-diameter ratio of 38:1, and melted at a temperature of 120-150° C. The obtained melt is used as the inner and outer surface layers of the film (hereinafter referred to as A layer melt).
[0052] The polypropylene homopolymer and the cycloolefin copolymer were mixed in a ratio of 90:10 (mass ratio) as the raw material of the core layer structure (hereinafter referred to as B layer material). The B layer material was added into a twin-screw extruder with a length-to-diameter ratio of 38:1, melted at a temperature of 130-180°C, and the obtained melt was used as the core layer of the film (hereinafter referred to as B layer melt).
[0053] The above-mentioned A layer melt and B layer melt are filtered through a candle wick filter with a filtration accuracy of 20 μm in a ratio of 20:80 (mass ratio) and then enter a three-layer adapter, and then flow out through a three-layer hanger die to obtain a composite melt with a three-layer structure, wherein the thickness ratio of the upper structure melt (i.e., A layer melt), the core layer structure melt (i.e., B layer melt) and the lower structure melt (i.e., A layer melt) is 10:80:10.
[0054] The composite melt with the three-layer structure was rapidly cooled on a quench roller at 30°C under a wind knife with a wind pressure of 40 kPa and a wind knife gap of 1.5 mm to form a cast sheet. The cast sheet was then preheated by a roller at a temperature of 60-120°C (6 rollers, the temperature was set from low to high at 60°C-75°C-90°C-100°C-110°C-120°C) and then longitudinally stretched by 1.05 times, and then entered a transverse stretching oven for 90°C-13 The low-density high-shrinkage film is prepared by hot air preheating (preheating time 3-5s, film temperature gradually increased to 120°C) at 0°C (3 preheating zones + 3 stretching zones, temperature set from low to high is 90°C-110°C-130°C), followed by 6 times transverse stretching, and finally by heat setting treatment (4s) at 80-100°C (3 setting zones, temperature set from high to low is 100°C-90°C-80°C) and cooling treatment at 30°C to obtain the low-density high-shrinkage film.
[0055] Embodiment 2: A method for preparing a low-density high-shrink bottle film, comprising the following steps:
[0056] The terpolymer polypropylene and the organosilicon with a particle size of 0.8 μm are mixed in a twin-screw extruder with a mass ratio of 99.8:0.2 and an aspect ratio of 42:1 and an extrusion temperature of 120-160°C. The terpolymer polypropylene resin is accurately fed from the feed port by the twin screw, and the organosilicon is side-fed in the melt plasticizing zone of the extruder. Finally, the mixed melt is pelletized and dried underwater to obtain the raw material of the surface structure of the terpolymer polypropylene resin and the organosilicon mixed (hereinafter referred to as A layer material).
[0057] The above-mentioned A layer material is added into a twin-screw extruder with a length-to-diameter ratio of 40:1, and melted at a temperature of 130-160° C. The obtained melt is used as the inner and outer surface layers of the film (hereinafter referred to as A layer melt).
[0058] The polypropylene homopolymer and the cycloolefin copolymer were mixed in a ratio of 80:20 (mass ratio) as the raw material of the core layer structure (hereinafter referred to as B layer material). The B layer material was added into a twin-screw extruder with a length-to-diameter ratio of 38:1, melted at a temperature of 130-180°C, and the obtained melt was used as the core layer of the film (hereinafter referred to as B layer melt).
[0059] The above-mentioned A layer melt and B layer melt are filtered through a candle wick filter with a filtration accuracy of 30 μm in a ratio of 20:80 (mass ratio) and then enter a three-layer adapter, and then flow out through a three-layer hanger die to obtain a composite melt with a three-layer structure, wherein the thickness ratio of the upper structure melt (i.e., A layer melt), the core layer structure melt (i.e., B layer melt) and the lower structure melt (i.e., A layer melt) is 15:70:15.
[0060] The composite melt with the three-layer structure is rapidly cooled on a quench roller at 40°C, under a wind knife with a wind pressure of 60 kPa and a wind knife gap of 2 mm to form a cast sheet, and then the cast sheet is preheated by a roller at a temperature of 80-120°C and then stretched 1.1 times in the longitudinal direction, and then enters a transverse stretching oven and is preheated by hot air at 100-130°C and then stretched 7 times in the transverse direction, and finally subjected to a heat setting treatment at 90-100°C and a cooling treatment at 30-50°C to obtain the low-density high-shrinkage film.
[0061] Embodiment 3: A method for preparing a low-density high-shrinkage film, comprising the following steps:
[0062] The terpolymer polypropylene and the organosilicon with a particle size of 1.0 μm are mixed in a twin-screw extruder with a mass ratio of 99.9:0.1 and an aspect ratio of 48:1 and an extrusion temperature of 140-180°C. The terpolymer polypropylene resin is accurately fed from the feed port by the twin screw, and the organosilicon is side-fed in the melt plasticizing zone of the extruder. Finally, the mixed melt is pelletized and dried underwater to obtain the raw material of the surface structure of the terpolymer polypropylene resin and the organosilicon mixed (hereinafter referred to as A layer material).
[0063] The above-mentioned A layer material is added into a twin-screw extruder with a length-to-diameter ratio of 46:1, and melted at a temperature of 120-150° C. The obtained melt is used as the inner and outer surface layers of the film (hereinafter referred to as A layer melt).
[0064] The polypropylene homopolymer and the cycloolefin copolymer were mixed in a ratio of 70:30 (mass ratio) as the raw material of the core layer structure (hereinafter referred to as B layer material). The B layer material was added into a twin-screw extruder with a length-to-diameter ratio of 48:1, melted at a temperature of 150-180°C, and the obtained melt was used as the core layer of the film (hereinafter referred to as B layer melt).
[0065] The above-mentioned A layer melt and B layer melt are filtered through a candle wick filter with a filtration accuracy of 40 μm in a ratio of 30:70 (mass ratio) and then enter a three-layer adapter, and then flow out through a three-layer hanger die to obtain a composite melt with a three-layer structure, wherein the thickness ratio of the upper structure melt (i.e., A layer melt), the core layer structure melt (i.e., B layer melt) and the lower structure melt (i.e., A layer melt) is 20:60:20.
[0066] The composite melt with the three-layer structure is rapidly cooled on a quench roller at 40°C, under a wind knife with a wind pressure of 40-80 kPa and a wind knife gap of 1-2 mm to form a cast sheet, and then the cast sheet is preheated by a roller at a temperature of 90-120°C and then stretched 1.2 times in the longitudinal direction, and then enters a transverse stretching oven and is preheated by hot air at 110-130°C and then stretched 8 times in the transverse direction, and finally subjected to a heat setting treatment at 80-90°C and a cooling treatment at 30°C to obtain the low-density high-shrinkage film.
[0067] Comparative Example 1: A method for preparing a petroleum-based PETG shrink film, comprising the following steps:
[0068] Petroleum-based PETG chips (brand SK 2012) of SK Chemicals Co., Ltd. of South Korea and petroleum-based anti-sticking PETG chips (brand MB 13) of Sukano Co., Ltd. were mixed in a mass ratio of 99.2:0.8, and then added into a twin-screw extruder to melt to obtain a uniform melt. The melt was filtered through a screen filter with a filtration accuracy of 1200 meshes and then entered an adapter, and then flowed out through a single-layer hanger die head, and formed into a cast sheet on a quenching roller at a temperature of 30° C. and under 10kV electrostatic adsorption, and then the cast sheet was preheated by a roller at 60-80° C. and then stretched longitudinally by 1.02 times, and then entered a transverse stretching oven and preheated by hot air at 80-110° C. and then stretched transversely by 4.6 times, and finally subjected to a heat setting treatment at 80° C. and a cooling treatment at 30° C. to obtain the petroleum-based PETG shrink film.
[0069] Comparative Example 2: A method for preparing a low-density high-shrinkage film, which differs from Example 1 in that terpolymer polypropylene and silicone with a particle size of 0.5 μm are mixed in a mass ratio of 99.4:0.6, and the remaining steps are consistent with Example 1.
[0070] Comparative Example 3: A method for preparing a low-density high-shrinkage film, which is different from Example 1 in that the particle size of the silicone is 1.2 μm, and the remaining steps are consistent with Example 1.
[0071] Comparative Example 4: A method for preparing a low-density high-shrinkage film, which is different from Example 1 in that: polypropylene homopolymer and cycloolefin copolymer are mixed in a ratio of 95:5 (mass ratio), and the remaining steps are consistent with Example 1.
[0072] Comparative Example 5: A method for preparing a low-density high-shrinkage film, which is different from Example 1 in that: polypropylene homopolymer and cycloolefin copolymer are mixed in a ratio of 50:50 (mass ratio), and the remaining steps are consistent with Example 1.
[0073] Comparative Example 6: A method for preparing a low-density and high-shrinkage film, which differs from Example 1 in that: in the composite melt with a three-layer structure, the thickness ratio of the upper structure melt (i.e., layer A melt), the core layer structure melt (i.e., layer B melt) and the lower layer structure melt (i.e., layer A melt) is 25:50:25, and the remaining steps are consistent with those of Example 1.
[0074] Test Example 1: This test example tests the density, shrinkage, stiffness (bending modulus), separation and hand-fitting properties of different types of shrink films prepared in the examples and comparative examples. The test method is as follows, and the test results are shown in Table 2.
[0075] Separation degree: First, cut the film into 3cm*3cm squares, put it into a 90℃ hot water bath to shrink for 10s and then take it out; break the bottle flakes into pieces of about 3cm*3cm; then, mix the shrunken film and bottle flakes in a ratio of 1:10 and add them to water, stir for 3-5 minutes, let it stand for 10 minutes, and then observe the separation of the film and bottle flakes.
[0076] Palm-fitting property: First, cut the film into a 10cm*10cm square, overlap two films together, dip a sterile dry cotton swab in the solvent, and evenly apply it between the two films. Press hard for 2s, let it stand for 5 minutes, and then use a knife to cut the sample into 15mm*10cm strips. Use a tensile testing machine to test the strength of the solvent palm-fitting position when the two films are separated.
[0077] Table 2-1 Performance comparison
[0078]
[0079]
[0080] Table 2-2 Performance comparison
[0081]
[0082] As shown in Table 2-1 and Table 2-2, the low-density high-shrinkage film prepared in the embodiment of the present invention and the 1.30 g / cm 3 Compared with the petroleum-based PETG shrink film with high density, the low-density high-shrink film obtained by the present invention has a high shrinkage capacity of 1.0 g / cm 3 The following density can be successfully separated from PET bottle flakes in the physical recycling process, and the two have similar shrinkage rates, but the film prepared by the present invention has a density that can be separated from PET bottle flakes.
[0083] By comparing the performance of the low-density, high-shrinkage film obtained in Example 1 with the films prepared in Comparative Examples 2-6, it can be seen that the present application successfully prepared a low-density, high-shrinkage shrinkage film through a specific raw material composition and preparation method, and the film has a high bending modulus and a certain stiffness, which can ensure smooth labeling when used as a label material.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low-density high-shrinkage film, characterized in that: It comprises a core layer structure and a surface layer structure arranged on the surface of the core layer structure; The raw materials of the core layer structure include polypropylene homopolymer and cycloolefin copolymer; the raw materials of the surface layer structure include terpolymer polypropylene and silicone; The density of the low-density high-shrink film is less than 1.0 g / cm 3 , the transverse shrinkage rate in a 90℃ water bath for 10s is ≥70%.
2. The low-density high-shrinkage film according to claim 1, characterized in that: The thickness ratio of the upper surface structure, the core layer structure and the lower surface structure of the low-density high-shrink film is 5-10:80-90:5-10, preferably 10-20:60-80:10-20; Preferably, the thickness of the low-density high-shrinkage film is 50-100 μm; Preferably, the density of the low-density high-shrink film is 0.92-0.99 g / cm 3 .
3. The low-density high-shrinkage film according to claim 1, characterized in that: In the core layer structure, the mass ratio of polypropylene homopolymer to cycloolefin copolymer is 60-90:10-40; Preferably, the polypropylene homopolymer has a crystallinity of 60-80%, a melt flow rate of 5-20 g / 10 min at 230° C. and 2.16 kg, an elastic modulus of 2000-3000 MPa, and a Vicat softening point of 130-170° C.; Preferably, the cycloolefin copolymer has a melt flow rate of 5-20 g / 10 min at 230° C. and 2.16 kg, and a density of 0.92-0.99 g / cm 3 , the glass transition temperature is 110-150℃.
4. The low-density high-shrinkage film according to claim 1, characterized in that: In the surface structure, the content of organic silicon is 0.1-0.5% of the total mass of the surface structure; Preferably, the particle size of the organosilicon is 0.5-1.0 μm; Preferably, the organosilicon includes one of vinyl silane, amino silane and methacryloxy silane; Preferably, the terpolymer polypropylene has a melt flow rate of 3-10 g / 10 min at 230° C. and 2.16 kg, and a melting point of 130-170° C. The terpolymer polypropylene is ethylene-propylene-1-butene terpolymer polypropylene, and the content of ethylene and butene-1 in the terpolymer polypropylene is 10-30 wt%.
5. A method for preparing a low-density high-shrinkage film according to claims 1-4, characterized in that: include: The organic silicon and the terpolymer polypropylene are melt blended and extruded and then pelletized to obtain the raw material of the surface structure; The raw material of the core layer structure is obtained by mixing the polypropylene homopolymer and the cycloolefin copolymer according to a certain proportion; The raw materials of the surface layer structure and the raw materials of the core layer structure are melted, cast, longitudinally stretched and transversely stretched to obtain a low-density high-shrinkage film.
6. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: using a twin-screw extruder with a length-to-diameter ratio of 40-52:1, accurately feeding ternary copolymer polypropylene from a feed port through the twin-screw, side-feeding silicone in a melting and plasticizing zone of the twin-screw extruder according to a proportion, the extrusion temperature being 120-180°C, and underwater pelletizing and drying the extruded mixed melt to obtain the raw material of the surface structure.
7. The preparation method according to claim 5, characterized in that: The melting comprises using a twin-screw extruder with a length-to-diameter ratio of 38-46:1 to melt and plasticize the raw materials of the surface layer structure and the raw materials of the core layer structure respectively, and the extrusion temperature is 130-200° C.; Preferably, the cast sheet includes the raw materials of the surface structure and the raw materials of the core structure, and the melts are filtered and then flow into the adapter and the die head, and then cooled on a quenching roller at 30-50° C. under a wind knife with a wind pressure of 40-80 kPa and a wind knife gap of 1-3 mm to form a cast sheet; Preferably, the longitudinal stretching comprises longitudinally stretching the cast sheet by 1.01-1.6 times after preheating, and the temperature of the longitudinal stretching is 60-100°C; preferably, the preheating is preheating the cast sheet by a roller at 60-120°C; Preferably, the transverse stretching comprises preheating the longitudinally stretched film again and then stretching it transversely by 6.0-10.0 times, and the transverse stretching temperature is 80-120 degrees Celsius; preferably, the preheating temperature of the preheating again is 90-130°C; Preferably, after the transverse stretching is completed, a low-density high-shrinkage film is obtained by heat setting treatment and cooling treatment; wherein the temperature of the heat setting treatment is 80-100°C, and the temperature of the cooling treatment is 30-40°C.
8. Use of the low-density high-shrink film according to any one of claims 1 to 4 or the low-density high-shrink film prepared by the preparation method according to any one of claims 5 to 7 in bottle label materials; Preferably, the density of the bottle is greater than 1g / cm 3 , further preferably, the bottle is made of polyethylene terephthalate.
9. A label, characterized in that: The low-density high-shrinkage film described in any one of claims 1 to 4 or the low-density high-shrinkage film prepared by the preparation method described in any one of claims 5 to 7 is made into a sleeve and is sleeved around the outer periphery of the packaging object.
10. The label according to claim 9, characterized in that The packaging object is a bottle, preferably a beverage bottle, and the material of the beverage bottle is ethylene terephthalate; Preferably, during the preparation of the sleeve, a solvent is used to self-bond the low-density high-shrinkage film together. Further preferably, the solvent is selected from at least one of tetrahydrofuran, chloroform and acetone.
Citation Information
Patent Citations
Low-temperature heat-seal shrinking packaging film used for cigarettes and manufacturing method thereof
CN105619990A
Low-density heat shrinkage film for labels, preparation method and application thereof
CN117400612A
Polypropylene-based heat-shrinkable film
CN118922482A
Film for shrinkable label
JP2004025458A
Heat shrinkable polyolefin film improved in heat resistance
JP2005193586A
Cited By
Label film with strong printing ink adaptability, low haze and low density as well as preparation method and application of label film
CN121133244A